(untitled) (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2023)
The title of this project, “An-icon,” refers to “images that deny themselves.” Virtual reality may be viewed as a typical, though not exclusive, case able to illustrate this kind of image: we know we have crossed the threshold of an environment that consists of images (ontologically), but we experience it (phenomenologically) as if it were a real environment. Something similar can be said about immersivity, but reversing the perspective: we are (ontologically) immersed in reality (virtual or non-virtual), but (phenomenologically) we know and say we are, and for this very reason we reject the idea that we are simply immersed in an environment. This applies first and foremost to our experience in general, regardless of the status of the experiences we gain through virtual reality (VR), augmented reality (AR) or mixed reality (MR). And yet, within this very general condition, human beings have over time created environments and works that carve out zones of “special immersivity,” so to speak, dedicated to immersion. What are we looking for in VR immersivity? Are new immersive technologies merely refinements of older techniques, or can they affect our relationship with ourselves, reality, and others in novel ways? What are artistic practices called on to do when faced with such new technological practices?